Female and male entrepreneurs in Germany: How did the coronavirus pandemic affect their businesses? - Rosemarie Kay; Friederike Welter (Institut für Mittelstandsforschung (IfM) Bonn, 2021)
Restrictions in the wake of the coronavirus pandemic have affected and continue to affect the operations of entrepreneurs. A wide range of support measures were designed to mitigate their consequences. This paper traces the economic development in the various sectors and provides an overview of the support measures. Based on the specifics of women's businesses, first answers will be given to the question whether women entrepreneurs and the businesses they run are particularly affected by the coronavirus crisis and whether they are supported in an appropriate way in overcoming the crisis. – – Einschränkungen im Zuge der Corona-Pandemie trafen und treffen auch die Tätigkeit von Unternehmerinnen und Unternehmern. Vielfältige Unterstützungsmaßnahmen sollen deren Folgen abmildern. Dieser Beitrag zeichnet die wirtschaftliche Entwicklung in den verschiedenen Branchen nach und gibt einen Überblick über die Unterstützungsmaßnahmen. Ausgehend von den Spezifika der von Frauen geführten Unternehmen wird danach gefragt, ob Unternehmerinnen und die von ihnen geführten Unternehmen in besonderer Weise von der Coronakrise betroffen sind und sie in angemessener Weise bei der Krisenbewältigung unterstützt werden.
Keywords: E60; J16; O10; 330; entrepreneurs; gender; coronavirus pandemic; turnover development; support measures